Kinetics and thermodynamics of the process of hydrodesulfurization of Shubarkol coal hydrogenate - Ordabaeva, A.T.; Akhmetkarimova, Zh.S.; Meiramov, M.G.; Khrupov, V.A.; Muldakhmetov, Zh.H.; Dusekenov, A.M.; Yun, Ma Feng (KSU Publ., 2017)
When processing coals and oils containing sulfur compounds, the resulting fuel components do not meet the requirements of the State standards for sulfur content. Sulfur affects negatively the quality of the target product and makes processing difficult, therefore hydrodesulfurization of coal hydrogenates and oils is an important stage before further processing. Sulfur compounds are very harmful impurities for liquid products (hydrocarbons). They are toxic, give an unpleasant smell to liquid products, affect detrimentally the antiknock properties of gasolines, promote resin formation in internal combustion engines and, most importantly, cause corrosion of metals. Therefore, the presence of these substances is extremely undesirable and unacceptable. There has been researched the process of hydrodesulphurization of hydrogenates of the coal from Shubarkol Deposit in the presence of catalyst of pyrite and natural zeolite. Using the method of equilibrium-and-kinetic analysis there have been calculated the rates of the process of hydrodesulphurization of liquid products and Gibbs energy that are necessary for improvement of process-dependent parameters of hydrofining of liquid products of hydrogenation. It is indicated that the optimum time of the process of hydrodesulphurization is 15–25 minutes. The content of sulfur in the fraction under 200 ºC is 0.043 per cent and in the fraction of 200– 300 ºC is 0.065 per cent and that indicates a high degree of hydrofining of hydrogenate in the presence of the above catalyst. A high value of ΔG (in absolute value) indicates a high thermodynamic probability of hydrodesulfurization process in the given temperature range. These data are necessary for the development of recommendations for determining the optimal conditions for the process.
Шұбаркөл көмір гидрогенизатының гидросульфирлеу үрдісінің термодинамикасы мен кинетикасы
Кинетика и термодинамика процесса гидрообессеривания гидрогенизата шубаркольского угля
Keywords: hydrodesulfurization; hydrogenizat; kinetic analysis equilibrium